Development and evaluation of a community-based buprenorphine treatment intervention - Aaron D. Fox; Nancy L. Sohler; Taeko Frost; Carolina Lopez; Chinazo O. Cunningham (BMC, 2017)
Abstract Background The majority of Americans with opioid use disorder remain out of treatment. Operating in 33 states, Washington DC, and Puerto Rico, harm reduction agencies, which provide sterile syringes and other health services to people who inject drugs, are a key venue to reach out-of-treatment opioid users. Aiming to link out-of-treatment individuals with opioid use disorder to buprenorphine treatment, we developed a community-based buprenorphine treatment (CBBT) intervention in collaboration with New York City harm reduction agencies. Methods Intervention development included formative data collection, feasibility testing at one harm reduction agency, and pilot testing for preliminary effectiveness at a second harm reduction agency. We used a pre-post design for both feasibility and pilot testing. In the CBBT intervention, we trained harm reduction agency staff to provide (1) buprenorphine education, (2) motivational interviewing, (3) referrals to buprenorphine-prescribing doctors, and (4) treatment retention support. We assessed feasibility by measuring staff satisfaction with the intervention and changes in knowledge about buprenorphine. We assessed preliminary effectiveness by comparing rates of buprenorphine initiation among groups of harm reduction agency clients before and after intervention implementation. Results Among staff members at the first harm reduction agency, knowledge increased from 52% correct answers pre-intervention to 79% correct post-intervention. Among clients at the second harm reduction agency, initiation of buprenorphine treatment was low and did not differ between pre- and post-intervention groups. Conclusions The CBBT intervention was feasible and well-received, but initiation of buprenorphine treatment among harm reduction agency clients was low. More robust interventions may be necessary to increase initiation of buprenorphine treatment.